Epitaxial YBa2Cu3O7−x nanocomposite thin films from colloidal solutions. (16th November 2015) - Cayado, P; De Keukeleere, K; Garzón, A; Perez-Mirabet, L; Meledin, A; De Roo, J; Vallés, F; Mundet, B; Rijckaert, H; Pollefeyt, G; Coll, M; Ricart, S; et al.
Abstract: A methodology of general validity to prepare epitaxial nanocomposite films based on the use of colloidal solutions containing different crystalline preformed oxide nanoparticles ( ex situ nanocomposites) is reported. The trifluoroacetate (TFA) metal–organic chemical solution deposition route is used with alcoholic solvents to grow epitaxial YBa2 Cu3 O7 (YBCO) films. For this reason stabilizing oxide nanoparticles in polar solvents is a challenging goal. We have used scalable nanoparticle synthetic methodologies such as thermal and microwave-assisted solvothermal techniques to prepare CeO2 and ZrO2 nanoparticles. We show that stable and homogeneous colloidal solutions with these nanoparticles can be reached using benzyl alcohol, triethyleneglycol, nonanoic acid, trifluoroacetic acid or decanoic acid as protecting ligands, thereby allowing subsequent mixing with alcoholic TFA solutions. An elaborate YBCO film growth analysis of these nanocomposites allows the identification of the different relevant growth phenomena, e.g. nanoparticles pushing towards the film surface, nanoparticle reactivity, coarsening and nanoparticle accumulation at the substrate interface. Upon mitigation of these effects, YBCO nanocomposite films with high self-field critical currents ( J c  ∼ 3–4 MA cm −2 at 77 K) were reached, indicating no current limitation effects associated with epitaxy perturbation, while smoothed magnetic field dependences of the critical currents at high magnetic fields and decreased effective anisotropic pinning behavior confirm the effectiveness of the novel developed approach to enhance vortex pinning. In conclusion, a novel low cost solution-derived route to high current nanocomposite superconducting films and coated conductors has been developed with very promising features.